Ilusi Kedamaian: Analisis Multidisiplin tentang Ideologi dan Dinamika Konflik Madara Uchiha dalam Naruto - Ahmad Rosikhul Fahmi; M. Luthfi Luqman Al Mustofa (IZUMI, 2025)
Madara Uchiha, the principal antagonist in Masashi Kishimoto’s Naruto series, embodies the paradox of seeking peace through authoritarian control. His character integrates psychological trauma, political philosophy, and narrative symbolism, reflecting real-world tensions between idealism and power. This study analyzes Madara’s internal-external conflicts, philosophy of peace, and narrative impact through an interdisciplinary lens (psychoanalytic, Marxist, and Machiavellian theories). Qualitative critical-scene analysis of manga volumes 55–72 (Naruto), focusing on 26 purposively sampled scenes (Vol. 65–67) depicting Madara’s trauma, ideology, and pivotal conflicts. Madara’s trauma (e.g., loss of his brother Izuna) fuels a pathological id-superego conflict, distorting his initial idealism into a Nietzschean will to power and Machiavellian realism. His "Tsukuyomi Infinite" project peace via mass illusion parallels modern authoritarianism (e.g., surveillance states). As a Hegelian antithesis to protagonist Naruto, Madara’s downfall exposes the ethical failure of power detached from empathy. Madara epitomizes how unhealed trauma and systemic injustice mutate into totalitarian ideology. His narrative serves as an allegory for the dangers of absolutist solutions to human suffering, affirming that true peace requires reconciliation not erasure of freedom and vulnerability.  gb777gb777slot gacorgb777gb777GB777GB777slot gacorslot gacor